Tumor promoting capacity of polymorphonuclear myeloid-derived suppressor cells and their neutralization - Groth, Christopher; Bitsch, Rebekka; Lasser, Samantha; Özbay Kurt, Feyza Gül; Kurzay, Annina; Petrova, Vera; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor (International journal of cancer, 2021)
Myeloid-derived suppressor cells (MDSC) represent a highly immunosuppressive population that expands in tumor bearing hosts and inhibits both T and NK cell antitumor effector functions. Among MDSC subpopulations, the polymorphonuclear (PMN) one is gaining increasing interest since it is a predominant MDSC subset in most cancer entities and inherits unique properties to facilitate metastatic spread. In addition, further improvement in distinguishing PMN-MDSC from neutrophils has contributed to the design of novel therapeutic approaches. In this review, we summarize the current view on the origin of PMN-MDSC and their relation to classical neutrophils. Furthermore, we outline the metastasis promoting features of these cells and promising strategies of their targeting to improve the efficacy of cancer immunotherapy.